2009
DOI: 10.1038/jid.2008.356
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-Based Targeting of Vaccine Compounds to Skin Antigen-Presenting Cells By Hair Follicles and their Transport in Mice

Abstract: Particle-based drug delivery systems target active compounds to the hair follicle and may result in a better penetration and higher efficiency of compound uptake by skin resident cells. As previously proposed, such delivery systems could be important tools for vaccine delivery. In this study, we investigated the penetration of solid fluorescent 40 or 200 nm polystyrene nanoparticles (NPs) as well as virus particles in murine skin to further investigate the efficacy of transcutaneously (TC) applied particulate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
82
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 127 publications
(89 citation statements)
references
References 34 publications
5
82
0
2
Order By: Relevance
“…200 nm were taken up by the LCs located around the hair follicles. 6 Moreover, TCI with antigen (gp100 protein) loaded chitosan NPs was shown to improve the survival of tumor bearing mice in comparison to antigen solution. 14 However, it remains unclear, if the particles were applied on intact or tape stripped skin.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…200 nm were taken up by the LCs located around the hair follicles. 6 Moreover, TCI with antigen (gp100 protein) loaded chitosan NPs was shown to improve the survival of tumor bearing mice in comparison to antigen solution. 14 However, it remains unclear, if the particles were applied on intact or tape stripped skin.…”
Section: Discussionmentioning
confidence: 99%
“…5 However, TF vaccination is usually performed after pre-treating the skin area by plucking hairs, waxing or cyanoacrylate (superglue) stripping. [6][7][8] Pre-treatment not only permeabilizes the skin by removing the upper layers of the SC, but also activates the innate immune system. 1 While both factors probably improve the immunogenicity of a topically applied vaccine, the disadvantage of the method is that permeabilization of the skin increases considerably the risk of infections.…”
Section: Introductionmentioning
confidence: 99%
“…The¯ndings suggested that follicular penetration had occurred. [15][16][17] However, as the stratum corneum was modi¯ed as animals grew older, a direct comparison between the follicular and the intercellular penetration was not possible. Subsequently, the Center of Experimental and Cutaneous Physiology developed a method permitting the follicular and intercellular penetration to be compared in vivo.…”
Section: Ca®eine Penetration By the Intercellular And Follicular Pathwaymentioning
confidence: 99%
“…[15][16][17] Newborn animals, which had not yet developed any hair follicles, were examined for the penetration of topically applied substances. These experiments were repeated on the same animals once their hair follicles had developed.…”
Section: Ca®eine Penetration By the Intercellular And Follicular Pathwaymentioning
confidence: 99%
“…Recently, a new study performed a similar experiment and 200 nm were able to aggregate and penetrate along the follicular duct and this was the major penetration pathway [131] displaying an increasing interest for a potential vaccination therapy. On the other hand, 40 nm nanoparticles were able to enter Langerhans cell in the hair follicles while 750 and 1500 nm could not.…”
Section: Skin Drug Deliverymentioning
confidence: 99%